Pengaruh Penggunaan Metode Demonstrasi Terhadap Keaktifan Belajar PAK Siswa Kelas VIII SMP Negeri 3 Lintongnihuta, Kabupaten Humbang Hasudutan Tahun Pembelajaran 2023/2024 - Gres Yosefin Sirait; Rusmauli Simbolong; Malani Simanungkalit; Taripar Aripin Samosir; Damayanti Nababan (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The aim of this research is to determine the effect of the demonstration method on the active learning of PAK class VIII students at SMP N 3 Lintongnihuta, Humbang Hasundutan Regency for the 2023/2024 learning year. The research hypothesis is: "There is a significant positive influence of the use of the Demonstration Method on the Learning Activeness of PAK Siwa class VIII SMP N 3 Lintongnihuta Kab. Humbang Hasundutan 2023/2024 Academic Year." The population is all class VII students of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year, totaling 192 people. The research sample was determined using a nonprobability sampling technique, namely purposive sampling, namely class VIII-2 students, totaling 32 people, as the experimental class using the exposure method and class VIII-3, totaling 32 people, as the control class using conventional methods. This research method is a quantitative approach with a true experimental design method and a post-test only control group design. The instrument used in this research was a 30-item questionnaire. Research data is analyzed using the Separated Variance t test formula. From the calculation results, the value of tcount = 4.716 > ttable(α=5%) = 1.671. The tcount value is in the curve area of rejection of H0 and acceptance of Ha. Thus, it can be concluded that the accepted research hypothesis is that there is a positive and significant influence of the use of the Demonstration Method on the Learning Activeness of PAK Siwa class VIII SMP N 3 Lintongnihuta Kab. Humbang Hasundutan 2023/2024 Academic Year.